The effects of silver ions and silver nanoparticles on cell division and expression of cdc2 gene in Allium cepa root tips - A. S. Fouad; R. M. Hafez (Biologia Plantarum, 2018)
The effects of silver nanoparticles (AgNPs), silver ions (Ag+), and polyvinylpyrrolidone (PVP) on mitosis and expression of a gene encoding cyclin-dependent kinase 2 (cdc2) in onion roots were compared. Three concentrations (5, 10, and 15 mg dm-3) were employed in combination with three incubation times (3, 6, and 9 h). PVP enhanced mitotic index and cdc2 expression. Both silver forms decreased mitotic index and cdc2 expression. Genotoxicity of both silver forms were indicated by three major distinguishable classes of chromosome aberrations: spindle disturbances, clastogenic aberrations, and chromosome stickiness. Concerning Ag+ treatments, significant enhancements in occurrence of any chromosome aberration type was associated with significant decrease in mitotic index. On the other hand, disturbed spindle in AgNPs treatments was observed even in absence of significant reduction in mitotic index suggesting that AgNPs inhibit cellular events occurring during mitosis to proceed normally rather than starting of cell division.